2022
DOI: 10.1002/ejoc.202200728
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed MIA‐Directed Acetoxylation of Benzylamines and Computational Study

Abstract: The direct acetoxylation of substituted benzylamines has been accomplished through methoxyiminoacyl (MIA)‐mediated Pd‐catalyzed C−H functionalization. A diverse array of phenylalanine substrates is amenable to this protocol, providing acetoxylation benzylamine derivatives with good to high efficiency. Computational results revealed that HOAc enhanced the stability of Pd−O bond, which obviously accelerate the reductive elimination step of the acetoxylation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…4, 151.1, 77.9, 64.7, 62.6, 44.0, 35.7, 32.3, 25.9, 24.2, 20.0, 9.9 3409,3223,2968,2940,1670,1639,1613,1522,1440,1365,1280,1160, 1049 cm −1 ; 1 H NMR (400 MHz, CDCl 3 ) δ = 6.82 (d, J = 8.0 Hz, 1H), 4.22−4.12 (m, 1H), 3.95 (s, 3H), 3.85−3.75 (m, 2H), 3.74−3.64 (m, 2H), 1.99 (s, 3H), 1.91− 1.72 (m, 2H), 1.22 (d, J = 6.8 Hz, 3H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ) δ = 162. 6,150.80,124.1 (q,J = 276.7 Hz),70.1,68.7 (q,J = 36.7 Hz),62.7,43.3,36.1,20.6,9.8 Procedure for Hydrogenation of MIA. To a solution of 2b, 2c, 2h(di) (1.0 equiv) and (Boc) 2 O (197 mg, 0.9 mmol, 3.0 equiv) in MeOH (0.2 M) was added 10% Raney Ni.…”
Section: Ethyl (E)-n-(2-(methoxyimino)propanoyl)-o-methyl-l-homoserin...mentioning
confidence: 99%
See 1 more Smart Citation
“…4, 151.1, 77.9, 64.7, 62.6, 44.0, 35.7, 32.3, 25.9, 24.2, 20.0, 9.9 3409,3223,2968,2940,1670,1639,1613,1522,1440,1365,1280,1160, 1049 cm −1 ; 1 H NMR (400 MHz, CDCl 3 ) δ = 6.82 (d, J = 8.0 Hz, 1H), 4.22−4.12 (m, 1H), 3.95 (s, 3H), 3.85−3.75 (m, 2H), 3.74−3.64 (m, 2H), 1.99 (s, 3H), 1.91− 1.72 (m, 2H), 1.22 (d, J = 6.8 Hz, 3H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ) δ = 162. 6,150.80,124.1 (q,J = 276.7 Hz),70.1,68.7 (q,J = 36.7 Hz),62.7,43.3,36.1,20.6,9.8 Procedure for Hydrogenation of MIA. To a solution of 2b, 2c, 2h(di) (1.0 equiv) and (Boc) 2 O (197 mg, 0.9 mmol, 3.0 equiv) in MeOH (0.2 M) was added 10% Raney Ni.…”
Section: Ethyl (E)-n-(2-(methoxyimino)propanoyl)-o-methyl-l-homoserin...mentioning
confidence: 99%
“…Then, γ-C(sp 3 )-H acetoxylation of alkylamides was afforded by utilizing the MIA group, 5 in which computational calculation has demonstrated that the electronic effect of directing groups has a significant influence via a five-membered cyclopalladium (OAc−Pd-C) complex on the reductive elimination step. Furthermore, ortho-C(sp 2 )-H acetoxylation 6 and dimethylation 7 were also accomplished with the MIA group. However, until now, γ-C(sp 3 )-H alkoxylation directed by MIA has not been reported.…”
Section: ■ Introductionmentioning
confidence: 99%